2019
DOI: 10.1016/j.pedhc.2019.04.017
|View full text |Cite|
|
Sign up to set email alerts
|

Attachment Disorders

Abstract: To obtain continuing education credit: 1. Read the article carefully. 2. Read each question and determine the correct answer. 3. Visit PedsCE SM , ce.napnap.org, to complete the online Posttest and evaluation. 4. You must receive 70% correct responses to receive the certificate. 5. Tests will be accepted until October 31, 2020. OBJECTIVES 1. Describe attachment theory. 2. Define attachment disorders in terms of types, risk factors, and treatment. 3. Discuss screening questions related to attachment disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The past study revealed that, the outcome expectations affect individuals' attachment to Airbnb (Lee et al, 2019) and eventually lead to their behavioural intentions (Yang et al, 2018). The fundamental concept of attachment is built on the idea of consumers forming an emotional and cognitive connection with others (Hornor, 2019). In the context of Airbnb, it can be explained as the emotional and cognitive connection that tourists feel towards Airbnb accommodation service.…”
Section: Unique Experience Expectation and Attachment To Airbnbmentioning
confidence: 99%
“…The past study revealed that, the outcome expectations affect individuals' attachment to Airbnb (Lee et al, 2019) and eventually lead to their behavioural intentions (Yang et al, 2018). The fundamental concept of attachment is built on the idea of consumers forming an emotional and cognitive connection with others (Hornor, 2019). In the context of Airbnb, it can be explained as the emotional and cognitive connection that tourists feel towards Airbnb accommodation service.…”
Section: Unique Experience Expectation and Attachment To Airbnbmentioning
confidence: 99%
“…Emotional neglect can be defined as a relationship pattern in which an individual’s affectional needs are consistently disregarded, ignored, invalidated, or unappreciated by a significant other [ 41 ]. Therefore, emotional neglect may be the essential risk factor for attachment disorders [ 42 ]. Moreover, emotional neglect self-reported in old age may reflect disorganized attachment, allowing us to speculate that attachment disorder may underlie the association between emotional neglect and lower gratitude.…”
Section: Discussionmentioning
confidence: 99%
“…In all these hypotheses, the best therapeutic approach is always the integrated one: psychotherapeutic (with cognitive-behavioural or strategic approach [25] and psychopharmacological, especially in the hypotheses of fullblown diagnosis of psychopathologies such as in the hypothesis of anxiety disorders [29][30], substance dependence [31,32], depressive disorders [32], post-traumatic stress disorder [33,34], disorder panic disorder [35,36], obsessive-compulsive disorder [37], eating disorders [38][39][40], suicidal tendencies [41,42] and personality disorders [43][44][45].…”
Section: Psychopathological Profi Les In Childhood and Adulthoodmentioning
confidence: 99%